Herbert George Wells. Socjalizm, utopia i melancholia - Franczak, Jerzy (Przestrzenie Teorii, 2023)
The article is a review of the most important works by Herbert George Wells in terms of the relationship between futurological vision, projected ideal and knowledge about the past. Wells is usually associated with a prospective attitude, with forecasting the future and modeling its desired image. Indeed, his science fiction novels, treatises and utopias try to answer the question of the paths of civilization’s development. But this work is accompanied by constant analysis of the past, correcting the scenarios of past events and shaping their new version. On the one hand, the retroactive formation of historical matter supports a utopia with a socialist profile, and on the other, it prevents its stabilization and closes it in the circle of left-wing melancholy, as described by Enzo Traverso. Some of the writer’s progressive ideas seem to be patient self-persuasion, others – such as fantasies about “fortunate disasters” – can be understood as attempts to escape from melancholy. Breaking free from its power, however, comes at a high price: it is the end of the socialist utopia, the abandonment of the idea of progress and the optimistic history of philosophy.